2011
DOI: 10.1128/iai.05182-11
|View full text |Cite
|
Sign up to set email alerts
|

Complement-Mediated Bactericidal Activity of Anti-Factor H Binding Protein Monoclonal Antibodies against the Meningococcus Relies upon Blocking Factor H Binding

Abstract: Binding of the complement-downregulating protein factor H (fH) to the surface of the meningococcus is important for survival of the organism in human serum. The meningococcal vaccine candidate factor H binding protein (fHbp) is an important ligand for human fH. While some fHbp-specific monoclonal antibodies (MAbs) block binding of fH to fHbp, the stoichiometry of blocking in the presence of high serum concentrations of fH and its effect on complement-mediated bactericidal activity are unknown. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(120 citation statements)
references
References 50 publications
3
117
0
Order By: Relevance
“…In contrast, no killing was observed when human complement was used. This result was not anticipated, because the high affinity of this mAb for fHbp might have been expected to prevent binding of hfH (present at high concentration in human serum) to the bacteria, thus resulting in uncontrolled activation of the alternative complement cascade and ultimately, enhanced bacterial killing (29). Additional work will be required to investigate the reasons underlying this lack of SBA activity, which has been observed for other mAbs (18).…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, no killing was observed when human complement was used. This result was not anticipated, because the high affinity of this mAb for fHbp might have been expected to prevent binding of hfH (present at high concentration in human serum) to the bacteria, thus resulting in uncontrolled activation of the alternative complement cascade and ultimately, enhanced bacterial killing (29). Additional work will be required to investigate the reasons underlying this lack of SBA activity, which has been observed for other mAbs (18).…”
Section: Discussionmentioning
confidence: 83%
“…Reaction mixtures contained approximately 400 colony-forming units (CFU), 20% human serum with no detectable bactericidal activity against the test isolates as complement source and serial dilutions of the anti-ACWY capsule antiserum or the anti-LPS mAb in serial 4-fold dilutions (stock 1 mg/mL). Bactericidal titers were defined as the dilution of serum or mAb resulting in 50% decrease of CFU/mL after 60 minutes incubation at 37°C compared to the CFU/mL in the control reactions at time 0 [24,25]. Antibody titers were log10 transformed, and bactericidal titers <10 were assigned the value 5.…”
Section: Methodsmentioning
confidence: 99%
“…Recent data suggest that antibodies against two different meningococcal proteins, fHBP and neisserial heparin binding antigen (NHBA), can cooperate to induce a bactericidal response (96). A recent study demonstrated that some antibodies have the ability to block fH binding to fHBP and that these antibodies can enhance complement-mediated bactericidal activity when small amounts of fHBP are expressed on the bacterial surface (74). The effect of human IgG subclass on the functional activity of anti-fHBP antibodies was recently examined, and it was shown that IgG3 monoclonal antibodies had higher bactericidal activity than IgG1 and IgG2 antibodies against an MnB isolate, whereas IgG1 antibodies were similar or superior to IgG3 antibodies against a mutant with increased fHBP expression (97).…”
Section: Biological Properties Of Monoclonal Antibodies Binding To Fhmentioning
confidence: 99%
“…The binding of fH to fHBP on the cell surface raises the concern that important vaccine epitopes may be shielded from bactericidal antibodies, both making a vaccine that targets fHBP less effective and possibly preventing the vaccine from generating an appropriate response. This is a hypothetical concern, as antifHBP antibodies are capable of both inhibiting binding of fH to fHBP and displacing fH from fHBP (74,75). It has also been suggested that binding of fH to the fHBP in the vaccine might reduce the availability of epitopes during the immunization process.…”
Section: Evidence That Human Factor H Is the Ligand For Fhbpmentioning
confidence: 99%
See 1 more Smart Citation